2005
DOI: 10.1016/j.jalgebra.2005.04.021
|View full text |Cite
|
Sign up to set email alerts
|

An inverse theorem for the restricted set addition in Abelian groups

Abstract: Let A be a set of k 5 elements of an Abelian group G in which the order of the smallest nonzero subgroup is larger than 2k − 3. Then the number of different elements of G that can be written in the form a + a , where a, a ∈ A, a = a , is at least 2k − 3, as it has been shown in [Gy. Károlyi, The Erdős-Heilbronn problem in Abelian groups, Israel J. Math. 139 (2004) 349-359]. Here we prove that the bound is attained if and only if the elements of A form an arithmetic progression in G, thus completing the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…If m = k − 1, then As far as the inverse problem modulo a prime is concerned, in [7] the inverse theorem of the Erdős-Heilbronn conjecture is proved. The proof however works only when adding two copies of A and, to the best of the author's knowledge, an inverse theorem for hˆA, h > 2, does not exist yet.…”
Section: Inverse Problemmentioning
confidence: 99%
“…If m = k − 1, then As far as the inverse problem modulo a prime is concerned, in [7] the inverse theorem of the Erdős-Heilbronn conjecture is proved. The proof however works only when adding two copies of A and, to the best of the author's knowledge, an inverse theorem for hˆA, h > 2, does not exist yet.…”
Section: Inverse Problemmentioning
confidence: 99%
“…G. Károlyi ([19], [20]) extended the Erdős-Heilbronn conjecture to general abelian groups. Theorem 5.2.…”
Section: Working With General Abelian Groupsmentioning
confidence: 99%
“…(ii) (G. Károlyi [20]) When |A| 5 and p(G) > 2|A| − 3, the equality |2 ∧ A| = 2|A| − 3 holds if and only if A is an arithmetic progression.…”
Section: Working With General Abelian Groupsmentioning
confidence: 99%
“…This is an extension of the Cauchy-Davenport theorem for finite groups. In [7,8], Károlyi established the following generalizaton of the the Erdős-Heilbronn problem:where A is a non-empty subset of the finite abelian group G. Subsequently, Balister and Wheeler [3] removed the restriction that G is abelian. In fact, they showed that |A ∔ B| ≥ min{p(G), |A| + |B| − 3}, for any non-empty subsets A, B of a finite group G.In this paper, we shall consider the extension of (1.1) for finite nilpotent groups.Theorem 1.1.…”
mentioning
confidence: 99%